SYSTEM OF INDICATORS CHARACTERIZING THE EFFICIENCY OF THE USE OF BUDGET FUNDS (Scientific journal of the Fergana State University, 2023)
The issue of spending budgetary funds should be treated in the same way as each member of society relates to spending their own funds. Unfortunately, it is alarming that the number of violations of the law on the use of budgetary funds has increased several times, as a result of which hundreds of billions of soums were spent inefficiently.The article proposes facts of violations in the spending of budgetary funds and a system of indicators that characterizes the effectiveness of the use of these funds.